The positions of my neighbors and the boys of the House of Prophethood and their role in spreading Islam - Hashim Jabur, Wisam (Journal of College of Education, 2021)
Influential figures emerged in Islamic history who had a clear position towards Islam, especially those positions that were on the side of the Noble Messenger Muhammad (peace and blessings of God be upon him and his family) and on the side of the pure family of the House (peace be upon them). The positions were not limited to personalities that have a political or tribal basis. As it was prevalent at that time, but included other social groups, and here we mean the maidservants and boys who served in the house of the Prophet (peace and blessings of God be upon him and his family) and his pure family (peace be upon them). Hence the importance of research in order to unmask the role played by that believing group in standing In addition to Islam and contributing to its dissemination, the research was entitled (The Attitudes of My Neighbors and Boys of the House of Prophethood and their Role in Spreading Islam) .Of course, it is not possible to cover all the positions due to their abundance, nor all the personalities due to their importance. Therefore, we chose a few influential personalities who had a prominent and important impact in supporting Islam and contributing to the dissemination of its political, social and intellectual thought.